Body Appearance Disciplinary Mechanisms and Procedures in Order to Build Beauty-Based Compliance for Sales Promotion Girls (SPG) at HP Cellular Sales Centers in Samarinda - Sri Murlianti; Dwi Samsudiani (Budapest International Research and Critics University, 2022)
Beauty does not always represent a woman's intelligence and skills, but in many studies beauty has become a serious issue that hinders women's progress in the public sphere. Naomi Wolf's study shows how women's struggles for beauty consume a lot of time and energy of working women, making it difficult to compete with men. In many fields of work, women are placed in fields that are expected to maximize appearance to achieve product sales targets. This study analyzes how a well-known HP shop in Samarinda builds a performance discipline system for Sales Promotion Girl (SPG)G so that they can always look perfect to persuade more buyers. The analysis was carried out using the perspective of 'the Discipline Body' by Michel Foucault. This study found that the shop created a selection mechanism, standardization, position control, and periodic reprimands to ensure that SPGs always look perfect based on beauty based on global beauty norms. This disciplinary system results in continuous compliance at the SPG level, even though the supervision is discontinuous